Proapoptotic N-truncated BCL-xL protein activates endogenous mitochondrial channels in living synaptic terminals - Jonas, Elizabeth A. (Proc Natl Acad Sci U S A, 2004)
Neuronal death is often preceded by functional alterations at nerve terminals. Anti- and proapoptotic BCL-2 family proteins not only regulate the neuronal death pathway but also affect excitability of healthy neurons. We found that exposure of squid stellate ganglia to hypoxia, a death stimulus for neurons, causes a cysteine protease-dependent loss of full-length antiapoptotic BCL-xL, similar to previous findings in mammalian cells. Therefore, to determine the direct effect of the naturally occurring proapoptotic cleavage product of BCL-xL on mitochondria, recombinant N-truncated BCL-xL was applied to mitochondria inside the squid presynaptic terminal and to purified mitochondria isolated from yeast. N-truncated BCL-xL rapidly induced large multi-conductance channels with a maximal conductance significantly larger than those produced by full-length BCL-xL. This activity required the hydrophobic C terminus and the BH3 domain of BCL-xL. Moreover, N-truncated BCL-xL failed to produce any channel activity when applied to plasma membranes, suggesting that a component of the mitochondrial membrane is necessary for its actions. Consistent with this idea, the large channels induced by N-truncated BCL-xL are inhibited by NADH and require the presence of VDAC, a voltage-dependent anion channel present in the outer mitochondrial membrane. These observations suggest that the mitochondrial channels specific to full-length and N-truncated BCL-xL contribute to their opposite effects on synaptic transmission, and are consistent with their opposite effects on the cell death pathway.